Simulations of copper single crystals subjected to rapid shear - Higginbotham, A; Bringa, E; Marian, J; Park, N; Suggit, M; Wark, J (2011)
We report on nonequilibrium molecular dynamics simulations of single crystals of copper experiencing rapid shear strain. A model system, with periodic boundary conditions, which includes a single dislocation dipole is subjected to a total shear strain of close to 10 on time-scales ranging from the instantaneous to 50 ps. When the system is strained on a time-scale short compared with a phonon period, the initial total applied shear is purely elastic, and the eventual temperature rise in the system due to the subsequent plastic work can be determined from the initial elastic strain energy. The rate at which this plastic work occurs, and heat is generated, depends on the dislocation velocity, which itself is a function of shear stress. A determination of the stress-dependence of the dislocation velocity allows us to construct a simple analytic model for the temperature rise in the system as a function of strain rate, and this model is found to be in good agreement with the simulations. For the effective dislocation density within the simulations, 7.8 10 11 cm - 2, we find that applying the total shear strain on time-scales of a few tens of picoseconds greatly reduces the final temperature. We discuss these results in the context of the growing interest in producing high pressure, solid-state matter, by quasi-isentropic (rather than shock) compression. © 2011 American Institute of Physics.